Tracking and modelling information diffusion across interactive online media. (25th January 2008) - Scharl, Arno; Weichselbraun, Albert; Liu, Wei
Information spreads rapidly across websites and other online media. The IDIOM research project analyses this process by identifying redundant content elements, mapping them to ontology concepts, and tracking their temporal and geographic distribution. Linguists define 'idiom' as an expression whose meaning is different from the literal meanings of its component words. Similarly, investigating information diffusion promises insights that cannot be inferred from individual network elements. Previous research often focused on particular media, or neglected important aspects of the human language. IDIOM addresses these gaps to reveal fundamental mechanisms of information diffusion across media with distinct interactive characteristics.